Effects of Sewage Sludges Contaminated with Chlorinated Aromatic Hydrocarbons on Sludge-Treated Areas (Soils and Sediments) - Ethel Eljarrat (The Scientific World Journal)
The fate of PCDDs, PCDFs, and PCBs in sewage sludges after different management techniques — such as agricultural application, land restoration, and marine disposal — was studied. Changes observed in the concentrations, in the ratio between PCDD and PCDF levels, and in the isomeric distribution suggest the influence of the sewage sludge on the sludge-treated areas (soils and sediments). Whereas land application techniques seem to produce no serious environmental consequences, marine disposal practices produce considerable increases in the levels of contamination in marine sediments.